ชีวิต ความตาย และภาวะใกล้ตาย :มุมมองของพระพุทธศาสนาและการประยุกต์ใช้ในการพยาบาล Life, Death and Dying: A Buddhist Perspective and Application in Nursing - เอกวุฒิวงศา, เรวัฒน์; เงางาม, ภาสกร; สุนทราภา, วรารัตน์; วุฒิสาร, ปริญญา (วารสารพยาบาลศาสตร์และสุขภาพ, 2014)
Although life and death happens to all humans, it is still difficult to understand and accept, especially death and incurable conditions. This article aims to present life, death, and dying from the Buddhist perspective.It can be concluded that the beginning of life consists of three factors, which are: 1) the union of father and mother , 2) the mother is in season , and 3) the gandhabba(stream of consciousness) is present . When life begins, it is composed of the five aggregates (Khan 5) . In terms of death, Buddhism divides death into many types; however, the real death from the Buddhist perspective is disincarnation. Because death can occur anytime, in order to face it peacefully Buddhism emphasizes caution and awareness of death at all times. Nevertheless, Buddhism also focuses on the mind(citta) before death, because apart from the impact of karma, it will determine the domain of life after death. These viewsnurses can be applied in real life and help dying patients to have mental calmness before they die.